2019
DOI: 10.22271/tpr.2019.v6.i2.34
|View full text |Cite
|
Sign up to set email alerts
|

Studies on farmland woody species diversity and their socioeconomic importance in Northwestern Ethiopia

Abstract: Study was conducted in the farmlands of Northwestern Ethiopia with the objective of assessing woody species diversity and their socioeconomic importance. Three sites representing three different elevations viz. highland, midland and lowland agroecology were selected. A total of 196 households were randomly selected to collect socioeconomic data. Data on woody species diversity in crop fields was collected by categorizing households as rich, medium and poor and from that categorized household the woody species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Hence, the more land a household owns, the higher the chance is to grow more trees in their land. e finding of this study is in line with Giday et al [52] and Aklilu et al [53] who reported that tree species richness increases as farm size increases. Asfaw and Hulten [54] and Abebe [41] also reported a positive relationship between farm size and tree species richness per farm and a similar relationship between wealth status and farm size in Southern Ethiopia.…”
Section: Influence Of Agroecological Zone and Wealth Status On Plant Diversitysupporting
confidence: 92%
“…Hence, the more land a household owns, the higher the chance is to grow more trees in their land. e finding of this study is in line with Giday et al [52] and Aklilu et al [53] who reported that tree species richness increases as farm size increases. Asfaw and Hulten [54] and Abebe [41] also reported a positive relationship between farm size and tree species richness per farm and a similar relationship between wealth status and farm size in Southern Ethiopia.…”
Section: Influence Of Agroecological Zone and Wealth Status On Plant Diversitysupporting
confidence: 92%
“…The result also showed that HHs within the rich wealth class has a larger average area of the home garden as compared to the HHs in the medium and poor wealth classes (Table 5). Giday Kidane et al(2019) and Mebrate Abiyot et al (2021) reported a positive relationship between farm size and tree species richness per farm and a similar relationship between wealth status and farm size in southern Ethiopia.…”
Section: Tree Diversity In the Crop Fieldsmentioning
confidence: 88%
“…Trees have impressive potential to improve soil fertility and forbid soil erosion in land management like farmland and watershed management [58][59][60][61]. For example, benefits of farmland woody plant species in the case of Northwestern Ethiopia are tremendous and soil fertility enhancement and management role indicates 35.14% among other benefits [62].…”
Section: Role Of Woody Plants In Soil Fertility Enhancementmentioning
confidence: 99%